Islamic spirituality and social responsibility in curtailing the workplace deviance - Bhatti, Omar Khalid; Alam, Muhammad Aftab; Hassan, Arif; Sulaiman, Mohamed (Emerald Group Publishing Limited, 2016)
Purpose – The current study aims to examine the relationship between Islamic spirituality (IS), Islamicsocialresponsibility(ISR)andworkplacedeviance(WD). Design/methodology/approach – Data were collected from 400 Muslim employees of 9 business groups in Pakistan from manufacturing and services industry. The structure equation modeling was usedtotestthehypotheses,andtheproposedmodelwasassessedthroughrenownedmodelfitindices. Findings – ThefindingsrevealedthatISandISRhelpcurtailWD.Thestudyalsoprovidesempirical support to the hypotheses that employees with high levels of IS and social responsibility will tend to avoiddeviantbehavioratworkplace. Originality/value – This study proposed IS and ISR as two possible stimuli that can help reduce mployee deviant behavior at workplace. Thefindings of the present study revealed that IS,as well as ISR, is inversely related to WD. The present results augmented the existing body of knowledge regarding workplace spirituality in the field of organization behavior and further enriched the WD theory by offering new empirical relationships from an Islamic perspective.